2018
DOI: 10.3168/jds.2017-13799
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Relationships among temperature-humidity index with rectal, udder surface, and vaginal temperatures in lactating dairy cows experiencing heat stress

Abstract: The objective of this study was to evaluate relationships between measurements of temperature-humidity index (THI) and rectal, vaginal, and udder surface temperatures in lactating cows exposed to heat stress (HS). In experiment 1, 12 multiparous and 8 primiparous Holstein cows experienced a THI ranging from 69 to 76 at 2000 to 1000 h and THI from 74 to 82 at 1000 to 2000 h (peaked at 82 from 1400 to 1800 h). Cows were exposed to HS 10 h daily for 21 d. Measurements of rectal temperature (RT) and udder surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 17 publications
2
32
0
1
Order By: Relevance
“…Similarly, temperature gradient variations in reproductive organs could affect the efficiency of ovulation and fertilization in female rabbits, swine, and humans [10]. Under heat stress conditions, development of the dominant follicle is suppressed [1], suggesting that suppression is due to a higher reproductive organ temperature [11]. Thus, reproductive organ temperature could be critical to ovulation and/or follicle development.…”
mentioning
confidence: 99%
“…Similarly, temperature gradient variations in reproductive organs could affect the efficiency of ovulation and fertilization in female rabbits, swine, and humans [10]. Under heat stress conditions, development of the dominant follicle is suppressed [1], suggesting that suppression is due to a higher reproductive organ temperature [11]. Thus, reproductive organ temperature could be critical to ovulation and/or follicle development.…”
mentioning
confidence: 99%
“…Previous studies have suggested that a strong relationship exists between T REC and T VAG in Bos indicus heifers (r = 0.92, p < 0.0001; Burdick et al [ 21 ]), pregnant dairy cows (R 2 = 0.90, p < 0.05; Hillman et al [ 19 ]), and lactating dairy cows (r = 0.81, p < 0.001, Vickers et al [ 18 ]; r = 0.92 ≤ 0.94, p < 0.001, [ 26 ]), although the strength of the relationship between T REC and T VAG decreased (r = 0.46, p < 0.001) during peak lactation [ 18 ]. Additionally Kaufman et al [ 20 ] showed that the relationship between T REC and T VAG increased from morning (1000 h, r = 0.47, p < 0.01) to afternoon (1500 h, r = 0.69, p < 0.01) in lactating dairy cows. The relationships identified within the current study are greater than those described by Hillman et al [ 19 ], Vickers et al [ 18 ], and Kaufman et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally Kaufman et al [ 20 ] showed that the relationship between T REC and T VAG increased from morning (1000 h, r = 0.47, p < 0.01) to afternoon (1500 h, r = 0.69, p < 0.01) in lactating dairy cows. The relationships identified within the current study are greater than those described by Hillman et al [ 19 ], Vickers et al [ 18 ], and Kaufman et al [ 20 ]. However, the relationships between T REC and T VAG within these studies were evaluated using intra-vaginal data loggers and hand-held thermometers to obtain time point measurements of T REC , with variable intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific calculation formula for THI is as follows (Sch€ uller et al 2013;Contreras-Jodar et al 2018;Kaufman et al 2018): THI = (1.8 9 T air + 32)À(0.55-0.55 9 RH) 9 (1.8 9 T air À26), where THI is the temperature humidity index, T air is the air temperature (°C), and RH is the relative humidity (%). We calculated the monthly variation in THI in the Inner Mongolia Autonomous Region by introducing the data from the Inner Mongolia Meteorological Service database.…”
Section: Thi and Wctmentioning
confidence: 99%